自噬在缺血性卒中后的作用 - 孙金梅 张拥波 李继梅 (中国卒中杂志, 2013)
Autophagy is an important way to remove the aging protein and damaged organelles. As a subtype of cell death, autophagy plays an important role in pathological and physiological conditions. There indeed is an autophagic phenomenon after ischemic insult in brain. Discussing the autophagy activation pathways and how to evaluate it in quality and quantity will be helpful to figure out the role of autophay after ischemic stroke.